Va rog sa ma ajutati:3×{5√6-√2×[(1+√3)(2+√3)-(5+√2)]}-5
Răspunsuri la întrebare
Răspuns de
1
1. (1+√3)(2+√3)=2+√3+2√3+3=2+3√3+3=5+3√3
2.(5+3√3)-(5+√2)=5+3√3-5-√2=3√3-√2
3.√2*(3√3-√2)=3√6-2
4.5√6-3√6+2=2√6+2
5.3*(2√6+2)=6√6+6
6.6√6+6-5=6√6+1
2.(5+3√3)-(5+√2)=5+3√3-5-√2=3√3-√2
3.√2*(3√3-√2)=3√6-2
4.5√6-3√6+2=2√6+2
5.3*(2√6+2)=6√6+6
6.6√6+6-5=6√6+1
Alte întrebări interesante
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Geografie,
10 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă
Engleza,
10 ani în urmă